Diseño in silico de una vacuna contra Virus de la Peste Porcina Africana - Escobedo Silva, José Eduardo; Guerrero Olazarán, Martha; Viader Salvado, José María; Galán Franco, Lucila Adriana; Gallegos López, Juan Antonio (Universidad Autónoma de Nuevo León, 2023)
Memorias